Perubahan Hukum Tata Negara di Indonesia Setelah Amandemen UUD 1945 - Feby Meilinda (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The 1945 Constitution has undergone four amendments. These amendments have brought significant changes to Indonesia's constitutional law. They encompass the transformation of the state from a unitary to a unitary state with broad autonomy, a shift in the governmental system from presidential to parliamentary-presidential, alterations in the presidential and vice-presidential election systems, changes in the judicial system, and modifications in the party system. This research aims to examine the changes in Indonesia's constitutional law following the amendments to the 1945 Constitution. Additionally, it seeks to analyze the impacts of these changes on Indonesia's constitutional system. The research employs a normative legal method, examining primary legal materials such as the 1945 Constitution and other related legislation concerning constitutional law. Furthermore, secondary legal materials such as books, articles, and journals related to constitutional law are also scrutinized. Based on the research findings, the alterations in Indonesia's constitutional law after the amendments to the 1945 Constitution have significantly impacted Indonesia's constitutional system, making it more democratic and ensuring greater respect for human rights.